Comparative study of the most efficient maximum power point tracking techniques for a photovoltaic system - I. M. Abdel-Qawee; H. G. Hamed; Maged N. F. Nashed; Ayman Y. Yousef; Khaled M. Hasaneen (Institute of Advanced Engineering and Science, 2019)
In Photovoltaic (PV) systems, maximum power point tracking (MPPT) is an important challenge which faces this system. In this paper, a comparative study between two high efficient MPPT control techniques is presented. These techniques are based on the incremental conductance (IC) method. The first technique is based on optimized PI-controller gains and the other is based on Fuzzy Logic Control (FLC). The comparison between the algorithms is investigated under different environmental conditions. The comparison criteria which are taken into consideration are: the percentage tracking factor (%TF), the tracking time, the ripple voltage in the steady-state, the dynamic response, and the complexity of implementation.